Pengaruh managemen kualitas pelayanan terhadap loyalitas dan kepuasan nasabah bank syariah - Afanin, Alfenda Nafiah (Maliki Interdisciplinary Journal, 2024)
This study aims to determine the impact of service quality on the loyalty and satisfaction of Islamic bank customers. This research uses the literature review method with the object of research being Islamic bank customers. The research findings show that Islamic banking has great potential for development, that its service quality has an impact on customer satisfaction and loyalty. Areas for improvement can be made in strengthening public financial literacy and development